An Empirical Study on Tourism Potentiality of Manipu - SANASAM, Lonashree; PRADHAN, Bibhutibhushan; MOHANTY, Sasmita (Journal of Environmental Management and Tourism, 2019)
Tourism is turning up to be an instrument of social, cultural and economic development world-wide as one of the fastest growing sectors. In country like India, rich natural beauty, cultural heritage, archaeological heritage sites, its diverse culture, languages, ethnicity, climatic conditions there is an enormous scope for tourism promotion. Manipur, “land of jewel” is one of the seven sisters in the North Eastern state of India with pleasant climate, rich nature, wildlife, cultural heritage, unique flora and fauna and vibrant and colourful festivals is a potential tourist destination. It has over 50 tourist spots, which can attract lots of tourist word-wide. Despite having so much to explore, tourism sector has not played its best to attract tourist. The objective of the study is to explore the reasons which is affecting the growth of tourism in Manipur by using fish-bone analysis and pareto analysis .